Sampling and Processing Methods Impact Microbial Community Structure and Potential Activity in a Seasonally Anoxic Fjord: Saanich Inlet, British Columbia - Torres-Beltrán, Mónica; Mueller, Andreas; Scofield, Melanie; Pachiadaki, Maria G.; Taylor, Craig; Tyshchenko, Kateryna; Michiels, Céline; Lam, Phyllis; Ulloa, Osvaldo; Jürgens, Klaus; Hyun, Jung-Ho; Edgcomb, Virginia P.; et al. (Frontiers in Marine Science, 2019)
The Scientific Committee on Oceanographic Research (SCOR) Working Group 144 Microbial Community Responses to Ocean Deoxygenation workshop held in Vancouver, B.C on July 2014 had the primary objective of initiating a process to standardize operating procedures for compatible process rate and multi-omic (DNA, RNA, protein and metabolite) data collection in marine oxygen minimum zones (OMZs) and other oxygen depleted waters. Workshop attendees participated in practical sampling and experimental activities in Saanich Inlet, British Columbia, a seasonally anoxic fjord. Experiments were designed to compare and cross-calibrate in situ versus bottle sampling methods to determine effects on microbial community structure and potential activity when using different filter combinations, filtration methods and sample volumes. Resulting biomass was preserved for small subunit ribosomal RNA (SSU or 16S rRNA) and SSU rRNA gene (rDNA) amplicon sequencing followed by downstream statistical and visual analyses. Results from these analyses showed that significant community shifts occurred between in situ versus on ship processed samples. For example, Bacteroidetes, Alphaproteobacteria and Opisthokonta associated with on-ship filtration onto 0.4 µm filters increased 5-fold compared to on-ship in-line 0.22 µm filters or 0.4 µm filters processed and preserved in situ. In contrast, Planctomycetes associated with 0.4 µm in situ filters increased 5-fold compared to on-ship filtration onto 0.4 µm filters and on-ship in-line 0.22 µm filters. In addition, candidate divisions and Chloroflexi were primarily recovered when filtered onto 0.4 µm filters in situ. Results based on rRNA:rDNA ratios for microbial indicator groups revealed previously unrecognized roles of candidate divisions, Desulfarculales, and Desulfuromandales in sulfur cycling, carbon fixation and fermentation within anoxic basin waters. Taken together, filter size and in situ versus on-ship filtration had the largest impact on recovery of microbial groups with the potential to influence downstream metabolic reconstruction and process rate measurements. These observations highlight the need for establishing standardized and reproducible techniques that facilitate cross-scale comparisons and more accurately assess in situ activities of microbial communities.